The poetics of multiple bodies and heteroclites in Oriana Duarte (Palíndromo, 2021)
This paper comes from a Masters research that identifies the self-portrait as a political discourse in the oeuvre of Oriana Duarte, in regards to a body-centred work, and its fluidityand deterritorialization. By a self-writing, the artist composes herself in and beyond herself, in a cyborg and hybrid existence that escapes the norms of a passive female body canonized in art. Drawing an artist life, Oriana constructs herself in multiple and heteroclite becomings, in dialogue with elements of nature and extrapolation of human condition, placing the body in theepicentre of the relationship.
Keywords: Oriana Duarte.; Body.; Heteroclites.; Contemporary art.